Efeito da dieta hipoprotéica, hiperglicídica em ratos na fase de crescimento sobre o perfil metabólico no animal adulto - Grassi, Patrícia Ceolin (2011)
Objective: Our purpose was to investigate the effects on metabolic and physiological parameters of the administration of a low-protein, high-carbohydrate diet (LPHC diet - 6% protein and 74% carbohydrate) to post-weaning rats for 45 days and the consequences of the reversion to a normal diet (30 days) after an initial period (15 days) of LPHC diet. Methods and Results: Male Wistar rats (~100g – 30 days) were divided into: i) N Group, submitted to control diet; ii) LPHC Group, submitted to LPHC diet for 45 days; iii) R Group, rats received LPHC diet during 15 days and then replaced by a control diet for 30 days. The control diet had 17% protein and 65% carbohydrate (93g-AIN). At the end of 45 days, there were determined the weight of the tissues, the lipid and glycogen content in liver, lipid content of white adipose tissue and plasma total protein, creatinine, urea, AST, ALT, glucose, cholesterol, triglycerides, fatty acid, insulin, glucagon, leptin, T3, T4, TNF-alpha and corticosterone. Data are presented as mean ± SEM of 5 - 10 rats (p ≤ 0.05) by Oneway ANOVA. The Lee index was similar between groups at end of treatment, but it was observed lower body weight in LPHC rats compared with N and R rats (N: 273.3 ± 10.4; LPHC: 222.5 ± 12.1; R: 262.1 ± 11.5 g). Total plasma proteins and urea were reduced by LPHC diet, but was recovered after reversion to a normal diet. The plasma creatinine (N: 0.5 ± 0.1; LPHC: 0.6 ± 0.1, R: 0.6 ± 0.1 mg/dL), postprandial triglycerides (N: 78 ± 6; LPHC: 99 ± 8; R: 106 ± 8 mg/dL) and T3 (N: 2.2±0.1; LPHC: 2.7±0.1; R: 2.6±0.1 ng/mL) levels were similar between groups submitted to protein restriction and higher in comparison to N group. Serum cholesterol (N: 119 ± 5; LPHC: 116 ± 4; R: 141 ± 4 mg/dL) and T4 (N: 13.2 ± 0.3; LPHC: 14.2 ± 0.4; R: 15.3 ± 0.3 ng/mL) were increased only in rats of R group. The other parameters were similar among the groups. Conclusion: Although some metabolic parameters altered by protein restriction were reversed after the nutritional recovery, other parameters, mainly related with metabolic syndrome, were impaired. This study reinforces the metabolic programming theory in periods after weaning.